Youth Participation in Sesame Production in Gwer West Local Government Area of Benue State, Nigeria - M.O, Agada; R, Jiriko; S. A, Nongu (International Journal of Sustainable Agricultural Research, 2020)
The study assessed youth participation in sesame production in Gwer West Local Government Area of Benue State, Nigeria. Primary data were collected from ninety three (93) randomly selected sesame youth farmers using a structured questionnaire. Data were analyzed using descriptive statistics (frequency, percentage and mean) and inferential statistics (correlation). Results of the study showed that participation of youths in sesame production was moderate in land preparation (M=2.39), planting (M=2.01), manual weeding (M=2.05) and harvesting (M=2.03) and low in pesticide application (M=1.98), herbicide application (M=1.96), fertilizer application (M=1.73, threshing (M=1.90), winnowing (M=1.85) and bagging (M=1.80). Farmers sourced information on sesame production mainly from friends/relations (80.6%). Constraints to youths’ participation in sesame production were insect and diseases attack (M=1.89), insufficient agricultural inputs (M=1.83), inconsistency in agricultural programmes for youths (M= 1.80), insufficient agricultural implements (M= 1.74), lack of technical assistance (M=1.72), lack of access to credit facilities (M= 1.72), weed control problem (M=1.66), and poor access to viable markets (M=1.59). Years of formal education (r= -218; p<0.36) and sesame farm size (r= 281; p<0.36) significantly influenced youths’ participation in sesame production in the study area. It was concluded that participation of youth farmers in sesame production was low, but this could be improved by making sesame farming attractive to young people through the provision of production resources, access to education, farm land, and viable markets.